Risks, costs and labour markets: Explaining cross‐national patterns of far right party success in European Parliament elections - Halikiopoulou, D; Vlandas, T (Wiley, 2015)
Does the economy affect patterns of far‐right party support across countries? This article reconceptualizes micro‐level analyses that focus on the effect of unemployment through a framework of costs, risks and the mediating role of labour market institutions. It then derives several hypotheses and tests them on the results of the previous three EP elections in all EU Member States. Findings from multiple regression analyses indicate that unemployment, real GDP growth, debt and deficits have no statistically significant effect on far‐right party support at the national level. By contrast, labour market institutions influence costs and risks: where unemployment benefits and dismissal regulations are high, unemployment has no effect, but where either one of them is low, unemployment leads to higher far‐right party support. This explains why unemployment has not led to far‐right party support in some European countries that experienced the severity of the 2008 eurozone crisis.